Cybernation of the feeling and intuition functions for the intelligent control system - G. G. Vorobjev; L. G. Dmitrenko (Открытое образование (Москва), 2016)
Now researches for creating an intelligent control system сonventionally refer to “neurocybernetics” or “black box cybernetics”. The first approach has not received a meaningful progress, because modeling of elements and structures of a brain has shown insufficiency of the modern knowledge of an alive brain.Black box cybernetics means that for the reception of the intelligent system it is correct enough to reproduce observable results of the intellectual processes, besides, it makes no difference how these results are obtained. Insufficient speed of the existing computers is the difficulty, associated with the second approach. However, a huge variety of the intellectual activity displays forces to recognize, that the black box cybernetics is also doomed to fail, since all the features of intelligence cannot be taken into account.In the present research, aiming at the principles’ development for functioning of the intelligent control system of a new generation, the following approach is applied: intelligent system behavior is correctly displayed by any psychological theory of the person, therefore, “cybernation” of some enough economical of them can have the universal intelligent system as the result. Analytical psychology by Karl Jung is chosen as the prototype theory.From the four mental functions, offered by Karl Jung, in this case feeling and intuition are chosen, besides, that functions of thinking and sensation are left without in-depth analysis and are only superficially described. It is connected with the restrictions of the number of publications, and consideration of the given functions requires the significant amount.The feeling function under the given descriptions by Karl Jung, develops the attitude of «egoism» of the system to subject – a thing, situations, to process, etc. However, as no attitude is valid action, the developed attitude for the observer is “the indicator” of the given function of the system, found in the knowledge base of “the natural operation” (or their sets), which can be applied to subject matter to get the features (positive or negative), acceptable in the current intellectual process.The basic purpose of the intuition function due to the descriptions of Karl Jung, is “revealing of the possibilities, put in the subject matter”. As no “revealing of possibilities” specifically pursues the achievement of particular goals (settling of the problem situations in the intelligent system), then by the intuition action the system adapts to possible development of events, external for the system, or to adequate changes of its own condition.By the joint action of the feeling and intuition the intelligent system has an opportunity to extend functioning in problem situations, i.e. at uncertainty – impossibility of use of rational thinking, as well as at “heavy” destructions of structure of the knowledge base of the system, having similar consequences.